AS REPERCUSSÕES DO PROGRAMA “O LÍDER EM MIM” NOS PROCESSOS DE APRENDIZAGEM SOCIOEMOCIONAIS E SUAS CONTRIBUIÇÕES PARA UMA EDUCAÇÃO HUMANIZADA - Lopes, Claudia Maria Sebalhos (2022)
The main objective of this study was to analyze the impacts of “The leader in me” Program in the teaching and learning processes and its contributions to a humanized education in a third grade group of elementary school at Batista School of Santa Maria, RS. The research is a case study with a qualitative approach. The study sample was composed by a third-grade elementary school teacher at Batista School of Santa Maria, RS, and the families (parents or guardians) of the studied class learners. Data collection was carried out in the second half of 2021. The instruments used in the research data collection were online questionnaires, which had the purpose of verifying the perception of how much “The Leader in Me Program" has contributed to the development of the students' leadership and checking their contributions to a humanized education. For analyzis of the collected data, the basic steps of Laurence Bardin's content analysis will be used. The study conducted pointed out that “The Leader in Me” program contributed in an important way to improving the development of the studied class learners, enabled systematization and organization of the socio-emotional foundation promoted by the effective change of behavior and acquisition of new habits and skills, observed by the regent of the studied class and the families of the learners. It was noticed that by adopting the leadership model at school, students started using this language not only in the classroom, but also among themselves and with their parents or guardians. In addition, the construction of a new culture of humanized education makes communication more effective and develops better relationships between students x educators, educators x school, school x family from the use of the language of the 7 habits proposed by the “Leader in Me”.